GENE-24. DNA METHYLATION SIGNATURES DETECTED IN A SERUM-BASED LIQUID BIOPSY DISTINGUISH FUNCTIONAL AND INVASIVENESS FEATURES IN PITUITARY ADENOMAS. (11th November 2019) - Wells, Michael; Sarraf Sabedot, Thais; Asmaro, Karam; Mosella, Maritza; Malta, Tathiane; Nelson, Kevin; Snyder, James; deCarvalho, Ana; Mukherjee, Abir; Bahn, Arti; Robin, Adam; Rosenblum, Mark; et al.
Abstract: Pituitary tumors are the second most common CNS neoplasia (~15%). Despite mostly benign and slow-growing, they may be nonfunctioning and invade surrounding structures resulting in significant comorbidities. Currently, classification of PT according to their risk for aggressiveness is mainly based on invasiveness detected by imaging methods and histopathological features which requires surgically resected tumor. Being able to detect molecular markers associated with tumor subtypes and behavior pre-surgically using minimally invasive approaches (blood draw) is desirable in these tumors and may help to address current diagnostic and therapeutic challenges. In tissue specimens, distinct DNA methylation patterns distinguish PT according to their functional status but their role in invasiveness is still unclear. We hypothesized that profiling cell-free DNA (cfDNA) released by PT into the bloodstream allow the identification of epigenetic markers associated with relevant clinicopathological features. Genome-wide methylome profile of paired serum cfDNA (EPIC array) and tissue from 13 patients with pituitary macroadenomas (9 males; median age: 62; 9 Nonfunctioning/4 functioning, 6 invasive/7 noninvasive) and 3 controls serum (patients with epilepsy). Unsupervised analysis of the serum methylome from patients harboring PT was distinct from controls and other diseases (hypopituitarism, glioma and colorectal cancer) and supervised analysis (Wilcoxon Rank-sum Test) identified significant differentially methylated probes (DMP) that segregated PT from control serum specimens. Nonfunctioning and invasive-specific DMPs identified in the serum also defined functional, and less prominently invasive status, in the tissue of an independent cohort of PT. This is the first study to show the feasibility to profile the serum methylome from patients with PT using cfDNA. In addition, we identified unique methylation signatures that distinguished PT according to functional and invasiveness subtypes. These results underpin the potential role of methylation profile and liquid biopsy as a noninvasive approach to assess clinically relevant molecular features in the serum of patients harboring PT.